Positional assembly of hemin and gold nanoparticles in graphene–mesoporous silica nanohybrids for tandem catalysis. Issue 2 (28th November 2014) - Lin, Youhui; Wu, Li; Huang, Yanyan; Ren, Jinsong; Qu, Xiaogang
Abstract : A hybrid catalyst in which two different types of enzyme mimics are positioned in spatially separate domains within a graphene–mesoporous silica support is presented. Abstract : Here, for the first time, a hybrid catalyst in which hemin and gold nanoparticles are positioned in spatially separate domains within a graphene–mesoporous silica support is presented. Specifically, monomeric hemin can be anchored on the inner exposed graphene surface of a graphene–mesoporous silica hybrid (GS) via π–π stacking interactions. After the assembly, such nanocomposites can function as a peroxidase mimic. Next, gold nanoparticles, which act as artificial glucose oxidase, can be conjugated to the functional NH2 groups present on the outer coated silica surface. As a result, the integrated catalysts containing multiple catalytic sites can be used to catalyze sequential reactions, without the aid of true enzymes. This work is an important step forward in positional assembly of biomimetic catalysts for artificially mimicking natural organelles or important chemical transformations in the future.